Formulation development and evaluation of a dual buffered chewable tablet of pantoprazole sodium - JAIN SURENDRA KUMAR; JAIN RUCHI; TAHILANI PRAVEEN; JAIN NILESH (International Journal of Pharma and Bio Sciences, 2019)
The present work aim to develop formulation for dual buffered chewable tablet of pataprazole sodium. Pantoprazole is used to treat certain stomach and esophagus problems (such as acid reflux). It works by decreasing the amount of acid your stomach makes. The study is designed to compare plainproton-pump inhibitors (PPIs)with buffered PPI on pH profile studies. By focusing on the use of proton-pump inhibitors (PPIs)combination with dual buffers of making it acid labile without any enteric coating of tablet or capsule or any sort of delayed release formulation. As we are focused on the problem of GERD and the symptoms associated with it, so it is necessary to deliver the drug by oral route; the notable disadvantage is degradation of the active ingredient by the low gastric pH leading to insufficient bioavailability. One of the manner in which we can protect the drugs from low gastric pH is to make use of buffers either in combination or in single combination with the drug. The buffers used in combination with the drug can be of sodium, magnesium and potassium. Various parameters (angle of repose, bulk density, carr’s index, hausner’s ratio)) were evaluated of the powder blend to calculate their flow properties, along with parameters which were performed in the evaluation of dual buffered chewable tablets showed satisfactory results and were in compliance with the standards mentioned in official compendium. All the formulations have shown both pre compression and post compression characters within acceptable limits. The chewable tablets were prepared by the method of direct compression using 14mm flat faced punches.All three formulations showed good results and FD-1 showed fast disintegration, better drug release and high % of drug content than FD-2 and FD-3. IR-spectroscopic studies indicated that FD-1 to FD-3 are compatible with each other and does not shown drug–excipients interactions. The optimized formulation follows first order kinetics.